2018
DOI: 10.1016/j.vaccine.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for vaccines against children’s diarrheal illness among mothers in Poland and Hungary

Abstract: Polish and Hungarian working mothers are more likely to vaccinate children against diarrheal illness than non-working mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the first study designed to comprehensively assess US adult preferences for HZ vaccines. Other studies, conducted on either general or specific (other than HZ) vaccine preferences among adults, have also shown that VE and OOP cost are key factors in vaccination decisionmaking [29][30][31][32][33][34][35][36][37]. Not all DCE studies have considered the same set of vaccine attributes.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study designed to comprehensively assess US adult preferences for HZ vaccines. Other studies, conducted on either general or specific (other than HZ) vaccine preferences among adults, have also shown that VE and OOP cost are key factors in vaccination decisionmaking [29][30][31][32][33][34][35][36][37]. Not all DCE studies have considered the same set of vaccine attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar surveys conducted in European countries have also shown that out-of-pocket expenses or vaccine cost, vaccine effectiveness, duration of protection and frequency of severe adverse effects were factors influencing parents when deciding about vaccination against RV for their children. 31,44 A survey of parents from Canada revealed that the main reasons why parents who had positive intentions yet did not have their child vaccinated were that they believed the child was receiving enough vaccines, that RV vaccine was not useful and RV vaccine was not included in the free public vaccination program. 32 Providing clarity on how to have access to the vaccine and its easy administration, the early successes of RV vaccination program introduction in 97 NIPs as of 2018 and its cost could potentially contribute to increasing the RV vaccination rate.…”
Section: Discussionmentioning
confidence: 99%
“…We have been able to provide overviews of full immunization programs developed using portfolio models. Examples include: showing the cost offsets and health gains of different dosing schemes using different vaccines for the same indication under a constrained budget (rotavirus vaccination) [41]; prioritising different intervention types to manage paediatric infections, and malaria [42,44]; demonstrating the benefit of child vaccination for working mothers with evidence of reduced work absenteeism [87]; improving QoC with vaccination and translating this into cost gains while maintaining QoC [50,60]; estimating the best combination of vaccination and screening to maximise cervical cancer reduction under a fixed budget [40]; and showing that extra budget does not guarantee substantial health gain in aging adults from PCV and/or influenza vaccination [43].…”
Section: Discussionmentioning
confidence: 99%